The effect of several L-amino acids on the inactivation process of Rana Ridibunda adult frog liver arginase - A. S. Shamirian; E. Kh. Barseghyan; M. A. Davtyan (ՀՀ ԳԱԱ հրատ.)
The effect of 8 L-amino acids (alanine, valine, leucine, isoleucine, γ-aminobutyric acid, lysine, proline, ornithine) on the Rana ridibunda adult frog liver arginase limited trypsinolysis process was studied. Ուսումնասիրված է 8 L-ամինաթթուների (ալանին, վալին, լեյցին, իզոլեյցին, γ-ամինակարագաթթու, լիզին, պրոլին և օրնիտին) ազդեցությունը Rana ridibunda հասուն գորտերի լյարդի սահմանափակ տրիպսինոլիզի ընթացքի վրա:Изучено влияние 8 L-аминокислот (аланин, валин, лейцин, изолейцин, γ-аминомасляная кислота, лизин, пролин, орнитин) на процесс ограниченного трипсинолиза аргиназы печени взрослых лягушек Rana ridibunda.
Keywords: Biology; Biochemistry